Musical awareness of French as a spoken language: elements for its didactic conditioning - Aubin, Sophie (Glottodidactica, 2022)
Musical awareness of the languages spoken in general and that of the French language in particular in the field of teaching French as a foreign language remains today weak, not generalized and much inferior to linguistic and cultural awareness. By placing oneself within the framework of the didactology-didactics of the music of the French language-culture, it appears that modes of conditioning of this spontaneous, intuitive and reflected musical consciousness can logically take their place in accordance with fundamental existence of the music of the French language produced in the spoken mode and of the need for the learner to master it.